The Effects of Inquiry-based learning on the Development of High School Biology Students’ Critical Thinking Skills in the UAE - Sabri, Sura (2019)
Background: Critical Thinking (CT) skills are believed to be essential skills that would enable people to improve the quality of their lives. Being a strong critical thinker is a major characteristic required for future job seekers. Educators agree that people can develop critical thinking skills through training and practicing core critical thinking skills. A suitable environment where CT skills can be implemented is in science education, as it is one of the strongest tools that can be utilized to train learners to use the core CT skills, which can be developed by the implementation of Inquiry Based Learning (IBL) strategies in science classrooms. Moreover, it has been established in educational research that learning through inquiry-based activities positively affects students’ learning experiences and promotes their self-regulatory learning skills. Purpose: The purpose of this study was to Investigate the implementation of inquiry-based learning in biology on the development of high school students’ critical thinking skills by investigating the current practices of IBL instructions and relating them to the development of students’ CT skills. Methods: This research followed the constructivist and postpositivist philosophies of research; the case study was employed with a multiple method design. The case study research included both quantitative and qualitative methods. The quantitative tool utilized was a non-experimental questionnaire and the qualitative tools included lesson observations, teachers’ interviews and document analysis of students’ artefacts. Results: The findings of this study revealed a lack of effective implantation of IBL instructions, as IBL application was limited to structured or guided inquiry and lacked appropriate assessment methodologies in the observed practices. Results also showed a variation in teachers’ ability to develop students’ CT skills within classroom instructions. The result of this study proposed a professional development program that targets science teachers’ skills in utilizing IBL instructions effectively to support students to develop CT skills. Implications Contributions: it was evident that science teachers were struggling to prepare IBL activities that would help deliver the required outcomes without compromising the quality of students’ understanding and their readiness to sit for standardized assessments. They were avoiding the use of open IBL activities due to concerns related to time management, the fear of losing control on students’ learning and the condensed curriculum that needs to be completed before standardized testing. The implementation of the suggested professional development programs will help the teachers to transform their teaching style with the confidence that their students will achieve the required learning outcomes.